Association of bilateral trans-syndesmotic lesion with logsplitter and syndesmosis instability with high ankle sprain in a young patient: a case report - Santisteban Avella, Fredy Yezid; Bolena Cely, Leidy; Martinez Perez , Maria Valentina; Alvarez Lopez, Claudia Milena; Naranjo Saenz , Angie Camila (Journal of the Foot & Ankle, 2025)
Dislocated fractures of the ankle are frequently associated with ligament injuries; between 20% and 45% of injuries of the distal tibiofibular syndesmosis occur in 6% to 16% of patients without associated fracture. These lesions can occur by different mechanisms: abduction, external rotation and dorsiflexion (Danis-Webber C), pronation and external rotation Lauge-Hansen and by vertical shearing, the latter being little described in the literature. Clinical presentation includes pain, edema, instability, restricted dorsiflexion, and functional limitation support and gait. The most characteristic symptom is pain over the tibiofibular ligaments. On physical examination, diagnostic suspicion is based on the presence of pain, edema, ecchymosis, and deformity at the ankle level. Diagnostic tests include different clinical signs, conventional and stress radiography, computed tomography, magnetic resonance imaging and fluoroscopy under anesthesia, in some cases), arthroscopy, and intraoperative clinical tests. We present the clinical case of a 21-year old female patient with right ankle dislocated fracture and bilateral injury of the distal tibiofibular syndesmosis following axial trauma to the lower limbs after a fall from a height of six meters. Level of evidence V; Case report.